Design of HOTS-Based Learning Evaluation to Improve Critical Thinking Skills and Achievements in Islamic Education - jazilurrahman jazilurrahman (Communautaire: Journal of Community Service, 2023)
This research aims to provide a deeper understanding of the Design of HOTS-Based Learning Evaluation to Improve Critical Thinking Skills and Achievement in Islamic Education (PAI). In order to obtain data from the research results, a qualitative approach and a case study method were employed. The research was conducted at Paiton Islamic Junior High School, Probolinggo, from September to Nopember 2023. Data collection techniques included participant observation, in-depth interviews, and documentation. Meanwhile, data analysis techniques used the Miles Huberman model, which involves data collection, data reduction, data display, and conclusion drawing. The results of this study indicate that the Design of HOTS-Based Learning Evaluation Improves Critical Thinking Skills and Achievement in Islamic Education (PAI) at Paiton Islamic Junior High School, Probolinggo, includes: Arranging Learning out comes (LO) of PAI, Training on HOTS-based learning evaluation, Implementation of School Exams with HOTS-Based Questions, and evaluation monitoring.